Problems of language, culture and spirituality in general explanatory dictionaries of Uzbek language - Rajabovich Mengliev, Bakhtiyor; Lolakhon Hamidovna, Nigmatova (International Journal of Psychosocial Rehabilitation, 2020)
Interpretation of terms of language, spirituality, and culture in Uzbek lexicography is not an easy one to interpret. In particular, Sh. Rakhmatullaev’s "Etymological Dictionary of the Uzbek Language" omits words from other languages in this annotated dictionary because of the purpose of etymological interpretation of the Turkic layer in the richness of the Uzbek literary language. This shows that the word spirituality is not really a Turkic word. Also, in the index dictionary of the eleventh-century work of Mahmud Kashghari’s "Devoni Lugotit Turk," the proverbs that make up the essence of the work, in general, reflect the qualities embodied in human spirituality.